1999
DOI: 10.1088/1126-6708/1999/02/002
|View full text |Cite
|
Sign up to set email alerts
|

Diffractive photoproduction of ups at HERA

Abstract: Predictions for the diffractive photoproduction of the Υ-family at HERA energies, within the framework of the analysis by Frankfurt, Koepf and Strikman, are presented. Two novel effects lead to a significant enhancement of the original calculation: the non-diagonal (or skewed) kinematics, calculated to leading-log(Q 2 ) accuracy, and the large magnitude of the real part of the amplitude. The resultant cross sections are found to agree fairly well with recent preliminary data from ZEUS and H1. A strong correlat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
125
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(129 citation statements)
references
References 11 publications
4
125
0
Order By: Relevance
“…(1) and (2) have demonstrated that interactions at the upper range of HERA energies in gluon-induced processes may be fairly close to the BBL in a wide range of impact parameters (see, e.g., [8,10]). This is consistent with an analysis [11] of current fits to HERA diffractive data, which leads to diffractive gluon densities which are significantly larger than the quark ones (see also [12]). …”
supporting
confidence: 90%
“…(1) and (2) have demonstrated that interactions at the upper range of HERA energies in gluon-induced processes may be fairly close to the BBL in a wide range of impact parameters (see, e.g., [8,10]). This is consistent with an analysis [11] of current fits to HERA diffractive data, which leads to diffractive gluon densities which are significantly larger than the quark ones (see also [12]). …”
supporting
confidence: 90%
“…Another critical test will be a measurement of the t-dependence of the Υ photoproduction at HERA which should be very close to the genuine two-gluon form factor. Note in passing that the t-slope of the elastic Υ photoproduction entered in the calculation of the total cross section of the γ + p → Υ + p reaction in [21]. Since at that time the data on the energy dependence of the slope of J/ψ production did not allow determination of α ′ for J/ψ we took it to be equal to zero.…”
Section: Comparison With the Datamentioning
confidence: 99%
“…We choose to plot results for the gluon since this is most relevant to small-x exclusive diffractive processes at HERA, for which it has been argued that the inclusion of skewedness (at least at LO in the unpolarized case) leads to an enhancement (see e.g. [21,22,33]). …”
Section: Fig 1 the Ratio Of The Unpolarized And Polarized Inputmentioning
confidence: 99%